IL27Rα Deficiency Alters Endothelial Cell Function and Subverts Tumor Angiogenesis in Mammary Carcinoma - Fink, Annika F.; Ciliberti, Giorgia; Popp, Rüdiger; Sirait-Fischer, Evelyn; Frank, Ann-Christin; Fleming, Ingrid; Sekar, Divya; Weigert, Andreas; Brüne, Bernhard (Frontiers in Oncology, 2019)
IL-27 regulates inflammatory diseases by exerting a pleiotropic impact on immune cells. In cancer, IL-27 restricts tumor growth by acting on tumor cells directly, while its role in the tumor microenvironment is still controversially discussed. To explore IL-27 signaling in the tumor stroma, we used a mammary carcinoma syngraft approach in IL27Rα-deficient mice. Tumor growth in animals lacking IL27Rα was markedly reduced. We noticed a decrease in immune cell infiltrates, enhanced tumor cell death, and fibroblast accumulation. However, most striking changes pertain the tumor vasculature. Tumors in IL27Rα-deficient mice were unable to form functional vessels. Blocking IL-27-STAT1 signaling in endothelial cells in vitro provoked an overshooting migration/sprouting of endothelial cells. Apparently, the lack of the IL-27 receptor caused endothelial cell hyper-activation via STAT1 that limited vessel maturation. Our data reveal a so far unappreciated role of IL-27 in endothelial cells with importance in pathological vessel formation.